Improved economics of HBsAg screening with commercial radioimmunoassay reagents. Issue 1 (January 1980) - Hopkins, R; Ross, S; Jordan, T; Watt, A D
Abstract : Commercial 125I anti-HBs was processed to yield a sixfold improvement in economy without significant loss of sensitivity or specificity. Additional polystyrene beads were coupled with commercially supplied anti-HBs. The modified assay (Mod-RIA) was compared with commercial RIA, EIA, and RPHA using established HBsAg panels. Mod-RIA was also compared with HEPATEST (RPHA) for screening 71 200 fresh blood donations during an 11.5-month period.